MANFAAT PEMBERIAN INSENTIF PAJAK PENGHASILAN DALAM KEPATUHAN WAJIB PAJAK UMKM - Rachmawati, Nurul Aisyah; Ramayanti, Rizka (Universitas Nusantara PGRI Kediri, 2016)
This study aims to examine whether tax incentives in PP 46 helpful to improve tax compliance of SMEs Tax Payer. In addition, this study also aims to determine whether the types of tax incentives between calculation, payment, and income tax reporting that have the greatest impact on improving tax compliance of SMEs Tax Payer. This study uses primary data obtained through the survey method. The sample of this study is SMEs Tax Payer in the South Jakarta. Data were analyzed by using SmartPLS software with Partial Least Square. This study found that tax incentives in PP 46 have positively impact on tax compliance of SMEs Tax Payer. Particularly compliance in terms of fulfillment of tax administration. Tax incentives in the form of income tax reporting provide the greatest impact on improving tax compliance of SMEs Tax Payer, compared to other insentives